The Genus Chitinophaga Isolated from Wanggameti National Park and Their Lytic Activities - Meliah, Siti; Kusumawati, Dinihari Indah; Lisdiyanti, Puspita (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTThe utilization of bacterial enzymes in commercial industry, agriculture, waste treatment and health is preferred over other sources like plants and animals sources because they provide many advantages for different applications. The genus Chitinophaga which was first described as chitinolytic Myxobacteria, known as chitin destroyer or chitin eater due to their capability to hydrolyze chitin. The present study aims to isolate, characterize, identify, and assay the indigenous bacteria from Wanggameti National Park for their lytic activity againts chitin, cellulose and protein as an initial step in bio-prospecting of Sumba Island. Eleven yellow pigmented isolates were obtained from soil and decayed wood samples using ST21 and Water Agar media. They formed halo on VY/2CX medium. Physiological charazterization showed that two isolates were able to produce catalase but none of them produced urease. The phylogenetic analysis based on 16S rRNA gene sequences indicated that all isolates belong to the genus Chitinophaga that consisting of Chitinophaga filiformis, Chitinophaga ginsengisoli, Chitinophaga pinensis, and Chitinophaga sancti. They were deposited in InaCC under the name InaCC B1254 to InaCC B1264. Qualitative analysis of their lytic activity exhibited that all strains were able to lyse chitin and cellulose. The strains with the highest chitinase and cellulase activity are InaCC B1260 and InaCC B1258 strains, respectively, both of them are C. pinensis. Hereafter, C. filiformis showed the highest proteolytic activity in skim milk casein amongs all strains at 1.14±0.08. Keywords: Chitinophaga, chitinase, cellulase, protease, Sumba